Pendampingan Strategi Pemasaran Dengan Digital Marketing Di Era Society 5.O Pada Pelaku Usaha - Andrianto Prasetya Nugroho; Etty Zuliawati Zed; Prasetyo Hari Sandi (Universitas Kristen Indonesia Toraja, 2023)
The problems faced by home businesses are quite diverse, ranging from operational management, employee performance, finance, to marketing, are tasks that must be completed by businesses. The challenge faced in this digitalization era is technological competition in terms of product marketing. The lack of utilization of existing digital marketing is one of the problems that exist for business actors who are doing competition. After Covid-19, consumers who are already familiar with the digital era are very used to the convenience of technological facilities that assist in every transaction activity that is carried out, such as when we are going to shop for clothes or food to choose the menu or model we want. want, we don't have to come to the seller's place, just look at the seller's social media, website, or e-commerce(Danny and Robin, n.d.). If business people can no longer follow the existing trends, then our products will lose competitiveness with other people's products that are easy to reach. In addition, it can have an impact on business development, business actors do not develop because income does not increase, the marketing area is not wide(Hidayati, Triajeng Pungkasanti, and Wakhidah 2020a). This becomes self-introspection in increasing mastery of digital marketing in this digitalization era. There are many kinds of marketing strategies, one of which is the use of quite a lot of digital marketing. This is an awareness for Mrs. Dina Marlina as the owner of the Basreng Teh Dina business that assistance is needed in using social media, be it Instagram, Facebook, or opening an e-commers account. in a store or app. other e-commers to become a product marketing tool. Departing from this, it is felt that assistance is needed regarding marketing strategies that focus on the use and utilization of digital marketing in the era of society 5.o so that the business owned is not inferior to other competitors.